Back to the Future: Star Trek and the Old French Epic. - Campbell, Kimberlee (Olifant, 2006)
The article explores the parameter of cyclicity in comparison with the chanson de geste in the science fiction television serial "Star Trek." It examines the debt of Star Trek to the explicitly medieval. It discusses the narrative cycle of the serial or the overall development and shape of which correspond quite closely to the medieval model of the chanson de geste. It also explores the serial's epic style.